The association between weight-adjusted-waist index and muscle strength in adults: a population-based study - Xu, Lihan; Zhou, Haojing (Frontiers in Public Health, 2024)
Background The relationship between the weight-adjusted-waist index (WWI) and grip strength, a crucial marker in assessing sarcopenia, lacks clarity. We aimed to explore the relationship between WWI and muscle strength across genders. Methods The cross-sectional study involved adults with complete data on WWI and grip strength from the 2011–2014 National Health and Nutrition Examination Survey. WWI was derived by dividing waist circumference by the square root of weight. Weighted multivariable logistic regression and smooth curve fitting techniques were used to examine the independent association and potential non-linear relationship between WWI and grip strength. A two-piecewise linear regression model was utilized to determine the threshold effect. Additionally, subgroup analyses and interaction tests were conducted. Results The study encompassed 9,365 participants, including 4,661 males and 4,704 females. Multivariate logistic regression analysis revealed a negative correlation between WWI and grip strength among males (β = −11.49, 95% CI: −12.38, −10.60, p < 0.001) as well as females (β = −2.53, 95% CI: −2.98, −2.08, p < 0.001). Subgroup analysis showed that the negative correlation of WWI with grip strength remained consistent across various age groups and levels of obesity for both males and females. Conclusion An increase in WWI correlates with reduced muscle strength in both males and females. WWI was negatively associated not only with muscle mass but also with muscle strength. WWI may serve as an assessment tool for sarcopenia, but further large-scale studies are needed to clarify causality.